Насінна продуктивність видів роду Bidens L. долини середнього Дніпра (в межах Лісостепу України) - Makhinya, L.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Results of studying of influence of habitat conditions on seed productivity parameters of genus Bidens species are given. Its substantial growth is shown at cultivation of plants in culture. Dependence of seed germination from their weight was shown.